Sexuality and partnership: Aspects of theological ethics in the field of marriage, unmarried and homosexual couples - Körtner, Ulrich H. J. (HTS teologiese studies, 2008)
The attitudes towards sexuality in Western society are undergoing dramatic change. One of the main problems sexual ethics has to deal with today is the question whether the church should acknowledge unmarried long-term relationships. The debate about the acknowledgement of homosexuality as a form of human sexuality equal to heterosexuality is aiming towards the acknowledgement of the equal status of homosexual partnerships and heterosexual marriages as a final consequence. In addition to these issues the article also discusses the issue of the blessing of unmarried or homosexual couples. In light of such public blessings and their liturgical form, the article aims to discuss the question about the promise such blessings holds according to Christian ethics.